Tumor induction by a transformation-defective polyoma virus mutant blocked in signaling through Shc - Bronson, Roderick (The National Academy of Sciences of the USA, 1997)
Transformation of cells in culture by polyoma virus requires integration of signals downstream of middle T–Shc and middle T-phosphatidylinositol 3-kinase interactions, but the same is not true for induction of tumors in the mouse. Thus, a middle T mutant defective in transformation and blocked in binding Shc is able to induce a broad spectrum of tumors after inoculation into newborn mice. The “tumor profile” induced by the mutant shows enhancement of tumors at some sites and reductions at others but otherwise resembles that induced by the wild-type virus. A nontransforming double-mutant blocked in binding phosphatidylinositol 3-kinase as well as Shc is severely affected but still induces some tumors. These results show that pathways that must cooperate to induce full transformation of cells in vitro can act independently and are to a large extent redundant in tumor induction.